Phenotyping Of Tomato Root Developmental Plasticity in Response to Salinity in Agar Plate System - Siti Nurzakirah, Suhaili (Universiti Malaysia Sarawak, (UNIMAS), 2022)
The architecture of the root system, especially its plasticity to adapt to different surroundings, is fundamental to the capability of plants to obtain and absorb food resources and thus assuring plant growth. The roots’ developmental responses to salinity stress in plants. In this study, phenotyping on germination of tomato plant root in agar plate system in response to salinity using ImageJ software was determined. Four different salt concentrations were used: 0 mM, 125 mM, 150 mM and 200 mM of NaCl. Four treatments with three replications, total 12 seeds were undergoing seed sterilization and growth into the Petri dish agar that contain different concentrations for 14 days. The ImageJ software measured and collected the data of the length of the main roots of the tomato seeds. The number of lateral roots was counted manually. Seed growth in Petri dish containing 0 mM of NaCl showed the longest length of the main roots and the greatest number of lateral roots. However, the seed in 150 mM of NaCl agar plate showed the second longest length of the main roots and the greater number of lateral roots. In conclusion, different salt concentrations in agar plate system affected the length of main roots and the number of lateral roots of MT1 tomatoes seed.